Cytochrome-C-oxidase expression in the subiculum and anterior thalamic nuclei of rats increases following training in an extrapolation of serial stimulus patterns task - da Silva, Daniel Giura; Torres-Cruz, Mateus; Helou, Ammir Yacoub; Xavier, Gilberto Fernando (Physiology & behavior, 2025)
•Rats extrapolate relying on serial stimulus patterns.•The subiculum and anterior thalamus contribute to extrapolation.•COX expression increases along with training for extrapolation.•Serial stimulus pattern training engages the subiculum and anterior thalamus. The brain continuously monitors the environment, comparing predictions based on memories of past regularities and action plans with current sensory information. The subiculum and the anteroventral thalamus have been proposed to play critical roles in this Generator of Predictions System (GPS). This study evaluated the hypothesis that cytochrome C oxidase (COX) expression changes in the subiculum and anterior thalamic nuclei of subjects exposed to training and testing in an extrapolation of serial stimulus pattern task that stimulates the generation of predictions. Shortly, male Wistar rats were trained to run through a straight alleyway to receive variable amounts of sunflower seeds. In each session (one session per day), the animals ran 4 successive trials, receiving different amounts of sunflower seeds in each trial. Subjects exposed to the monotonic pattern (M) received 14, 7, 3, and 1 sunflower seeds. Subjects exposed to the non-monotonic pattern (NM) received 14, 3, 7, and 1 sunflower seeds. The animals were trained for 20 sessions. In the 21st session, a fifth trial, never experienced before by the subjects, was added immediately after the fourth trial. An additional control group was not exposed to training in the task, allowing evaluation of COX expression in untrained subjects. Data revealed increased COX activity in the anteroventral thalamus, and in the ventral subiculum, all related to training in the NM, but not M, schedule of reward. Data also revealed reduced COX activity in the dorsal portion of the subiculum, restricted to subjects trained with the NM serial pattern. These figures suggest that the anteroventral thalamus and the ventral and dorsal subiculum are engaged in the acquisition of extrapolation of serial stimulus pattern tasks, thus opening novel avenues to studying neural brain circuits involved in generating predictions. One possibility, for instance, would be to evaluate the time course of these COX activations in association with training in the M and NM serial patterns.